Thermal and Mechanical Characteristics of Polymer Composites Based on Epoxy Resin, Aluminium Nanopowders and Boric Acid; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Nazarenko O. B. Olga Bronislavovna (2016, 2016)
Title screen